1883 Wis. Sess. Laws 369-70, ch. 152, ch. 6 [sic], § 8, pt. 16. - (:unkn) unknown (General Publisher, 1883)
To prevent and prohibit the manufacture, keeping or storing of nitro-glycerine, and to regulate the keeping and storing of gunpowder, gun cotton, burning fluids, coal oils and other dangerous explosive materials, in said city, and to provide for the inspection of illuminating oils and fluids.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER